PENGARUH CITRA MEREK, HARGA DAN KUALITAS PRODUK TERHADAP MINAT PEMBELIAN KONSUMEN - Harianja, Immanuela Nobella Sertina; Tjiptodjojo, Kartika Imasari (FEB Universitas Sam Ratulangi Manado, 2024)
The development and dynamic changes in trends have encouraged many industries to produce and offer products that are in line with the interests of consumers. One industry that has experienced a lot of progress is the fashion industry, especially shoes. Many local shoe industries have sprung up, one of which is Ventela. Ventela can produce shoes in large quantities with high standards so that it allows all groups to get shoes with high quality and prices that are still affordable so it is expected to encourage consumers to have an interest in purchasing local shoes, especially Ventela. This study aims to analyze whether brand image, price, and product quality can influence consumer purchase interest in Ventela products. The research sample of 140 respondents is the people of Bandung City who recognize and have bought Ventela shoes. The test was conducted using the simple linear regression analysis method with the result that the image of the brand and the quality of the product influence purchase intention, while the price has different results where it does not affect purchase intention.